Tentang Upaya Pencegahan Penularan Tuberculosis Paru Hubungan Tingkat Pengetahuan dengan Sikap Masyarakat - Yuni Anjelina; Fitriani Ningsih; Riska Ovany (Jurnal Surya Medika (JSM), 2022)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis is still a global public health problem that is a worldwide challenge. One of the causes of the lack of general knowledge in efforts to prevent the transmission of Tuberculosis is the lack of information and education from health workers or posyandu cadres about Tuberculosis, resulting in a lack of public knowledge about Tuberculosis. This study aims to explain "Correlation Between Knowledge Level And Attitude Of The Community About The Prevention Of Transmission Of Lung Tuberculosis" based on data through the Literature Review method. They are using the Literature Review method. Journal searches use an academic database, namely Google Scholar, published in 2017-2020 using Indonesian and English. Cross-sectional study design. Of the six journals, three journals state a relationship between knowledge and public attitudes about efforts to prevent Tuberculosis transmission p value = 0.05). At the same time, three journals say that there is no relationship between knowledge and measures to avoid Tuberculosis, but there is a relationship between attitudes and Tuberculosis prevention efforts. One of the causes of the lack of public knowledge in efforts to prevent the transmission of Tuberculosis is the lack of information and education from health workers or posyandu cadres about Tuberculosis, causing a lack of public knowledge about Tuberculosis. Other factors that can influence a person's attitude such as family, the influence of friends, personal experience, and information obtained from various sources.